PENGARUH MODEL PEMBELAJARAN KONSTRUKTIVIS BERBASIS PROYEK TERHADAP MEMBACA PEMAHAMAN SISWA KELAS V SDN 37 PANGKALPINANG - Elda; Agci Hikmawati; Nurjanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The inadequate reading comprehension abilities of the fifth graders at SDN 37 Pangkalpinang prompted this investigation. Reasons for students' lack of interest and drive in reading activities and the prevalence of traditional, teacher-centered methods of education contribute to their low level of competence. Because of this, the purpose of this research was to analyse how fifth graders at SDN 37 Pangkalpinang fared in reading comprehension after being exposed to a constructivist learning approach centred on projects. The research was quantitative in nature and used a pre-experimental design with a one-group pretest-posttest. Each of the two groups the experimental and the control consisting of all thirty-two fifth graders at SDN 37 Pangkalpinang made comprised the sample. Both the pre- and post-tests included a reading comprehension exam to gather data. After making that the data was normal and homogeneous, the analysts used SPSS version 22 to run an independent samples t-test to assess their hypotheses. Results showed that the data were normally distributed, with significance values larger than 0.05, for both the experimental and control groups' pretest and posttest scores in the normalcy test. A significant value of 0.672 (> 0.05) was generated by the homogeneity test, suggesting that the data variance was homogenous. The null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted based on the findings of the hypothesis testing, which showed a significance value (2-tailed) of 0.000 (< 0.05). It follows that fifth graders at SDN 37 Pangkalpinang benefit significantly from the project-based constructivist learning methodology in terms of their reading comprehension.